Dos ciudades en el cine y la literatura: Barcelona y Shangai - Castellani, Jean-Pierre (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2009)
The books of Juan Marsé give us a wide scope of points of view to study the relationship between real and imaginary cities. We take the example of the novel El embrujo de Shangai (1993) in which there is much more than Barcelona: like in other Marsé books, the author opposes a city where the characters live, Barcelona, and the other, Shangai which is transformed in myth by one of the republicans on his return from exile. We will put in evidence that cities are not only the setting sor the storytelling but that they also serve to the essential message of the novel: they express the deep disillusion of Marsé in Spain’s postwar and even when he writes his novel during the nineties. We will establish a relation with the eponymous movie adaptation by Trueba (2002) which will allow us to confirm the book’s originality and judge upon the movie’s qualities and its limits.